A midsummer night's fudge ebook - Coco, Nancy (Candy-Coated Mystery., 2022)
USA Today bestselling author After a summer celebration on Michigan's Mackinac Island ends in murder, hotel and fudge shop owner Allie McMurphy puts on her sleuthing hat . . . THERE'S NO SUGARCOATING A KILLER'S SCHEME During the Midsummer Night's Festival, Allie decides to take her bichonpoo, Mal, home to spare her furry little ears from the sounds of fireworks. But on her way back, Allie spots a body in the lake. Just minutes ago, Winona Higer was crowning the event's Queen—could the competition have really been that deadly? While she ponders the mystery the next morning, Allie prepares her favorite dark chocolate cherry fudge recipe. But she's soon recruited to sub for the late Winona and serve as parade float judge, among other duties. As she hears rumors and gossip, and learns of mean pranks and threatening notes, her instincts kick in—despite her boyfriend the cop's disapproval. Now, between managing a new hire and keeping the tourists filled with fudge, she's dealing with a case that's boiling over . . . Praise for Nancy Coco and the Candy-Coated Mysteries " Fun characters, quaint setting, mouth-watering recipes." — RT Book Reviews "Full of disguises, danger, and one determined amateur sleuth." — Fresh Fiction "A charming cozy." — Suspense Magazine Help support pet adoption—see details inside.